The Principal’s Strategy in Improving the Quality of Education Through the Flagship Program at Madrasah Aliyah Bilingual Batu - Sayyidatul Qory’ah; Ahmad Barizi; Fatia Ainur Rosyida; Kholis Aniyati (Al-Musannif, 2024)
The centralization of education policy in Indonesia has made educational materials and objectives lose their locality. The role and strategic steps of the principal are needed in implementing government regulations and the needs of a plural society. The purpose of this study was to analyze the strategy of the principal of Madrasah Aliyah (MA) Bilingual Batu in improving the quality of education through flagship programs. This qualitative study purposively selected the principal as the main informant, and teachers and students as supporting informants. Data were collected through observation, interviews, and documentation. The data analysis technique used descriptive analysis techniques with data validity tests using triangulation techniques. The results of the study showed that in order to make graduates able to compete in the international arena, bilingual programs (mastery of English and Arabic) were determined as flagship programs. To make the program a success, the principal took seven strategic steps: Establish a forum for channeling students’ interests and talents, form work teams, establish and maintain communication, improve teacher quality, provide infrastructure facilities, adjust the curriculum, and evaluate.